PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Noriko Thasya; Lisah Lisah; Angeline Angeline; Natasyah Gozal; Veronica Veronica (Universitas Medan Area, 2020)
This study aims to examine the effect of good corporate governance on corporate social responsibility. The Data that used in this research are all form of annual reports published by companies on the Indonesia Stock Exchange website. The population used is transportation sub Sector Company listed on the Indonesia Stock Exchange for the period 2014-2018 which amounted to 37 companies. Purposive sampling is used in this research to obtain 8 companies as research sample. The data were analyzed using multiple regression analysis using SPSS Version 25. The results of the research showed audit committee negatively influence on the corporate social responsibility, the board of commissioners has no influence on the corporate social responsibility, the institutional ownership negatively affected on the corporate social responsibility, and the independent commissioner no impact on the corporate social responsibility.